Handbook of green analytical chemistry - Guardia, M. de la (Miguel de la); Garrigues, Salvador (Chichester, West Sussex ; Hoboken : John Wiley & Sons, 2012)
The emerging field of green analytical chemistry is concerned with the development of analytical procedures that minimize consumption of hazardous reagents and solvents, and maximize safety for operators and the environment. In recent years there have been significant developments in methodological and technological tools to prevent and reduce the deleterious effects of analytical activities; key strategies include recycling, replacement, reduction and detoxification of reagents and solvents. The Handbook of Green Analytical Chemistry provides a comprehensive overview of the present state and recent developments in green chemical analysis. A series of detailed chapters, written by international specialists in the field, discuss the fundamental principles of green analytical chemistry and present a catalogue of tools for developing environmentally friendly analytical techniques.
Handbook of Green Analytical Chemistry; Contents; List of Contributors; Preface; Section I: Concepts; 1 The Concept of Green Analytical Chemistry; 1.1 Green Analytical Chemistry in the frame of Green Chemistry; 1.2 Green Analytical Chemistry versus Analytical Chemistry; 1.3 The ethical compromise of sustainability; 1.4 The business opportunities of clean methods; 1.5 The attitudes of the scientific community; References; 2 Education in Green Analytical Chemistry; 2.1 The structure of the Analytical Chemistry paradigm; 2.2 The social perception of Analytical Chemistry.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Green chemistry -- Handbooks, manuals, etc; Environmental chemistry -- Handbooks, manuals, etc; SCIENCE -- Chemistry -- Analytic; Grüne Chemie; Green Chemistry Technology; Chemistry Techniques, Analytical; Environmental chemistry -- Handbooks, manuals, etc; Environmental chemistry -- Industrial applications -- Handbooks, manuals, etc; Environmental chemistry; Green chemistry; Electronic books; Electronic books; Electronic books; Handbooks and manuals